(untitled) (Journal of Economic Research & Business Administration, 2019)
This article presents an economic analysis of the potential of small and medium-sized businesses in Kazakhstan. The purpose of the study is to study the dynamics of development of small and medium-sized businesses, and to assess its real role in the development of the country. The method of research is analytical grouping, comparing time series, building linear and point graphs, correlation analysis, which allowed to determine the presence, direction and form of relations between SMEs and a country’s GDP. The distribution of countries’ GDP by the share of SMEs in GDP is a figure similar to the normal distribution, with a peak of 50%. This makes it possible to understand that the optimal share of SMEs in GDP is 50%, but this does not guarantee GDP growth. The provision on the dual role of the institution of small and medium business (SME) in the economic system, where it simultaneously acts as a factor of its sustainability and a factor of modernization, is substantiated. This makes it difficult to build a state policy of support and development of SMEs, since within the framework of the policy being pursued, two opposing tasks have to be solved: stabilization and modernization. The results obtained in this article confirm the mutual influence and dependence of SMEs and the country’s GDP, and justify the shortcomings of government programs to promote SMEs in Kazakhstan.